Health inequities in medical crowdfunding: a systematic review - Cai, Yingying; Kamarudin, Syafila; Jiang, Xiaoyu; Zhou, Baiyu (BioMed Central, 2025)
Background: Medical crowdfunding has emerged as a popular strategy to offset healthcare expenses in contexts of limited insurance coverage. While often framed as a democratizing and accessible financial tool, growing evidence indicates that success is unevenly distributed, raising concerns about its role in exacerbating health inequities. Methods: A systematic review was conducted in accordance with PRISMA guidelines, drawing from PubMed, CINAHL, Embase, Web of Science, and Scopus. Of 1,462 screened records, 33 studies met the inclusion criteria. Guided by the PROGRESS framework, we extracted data on socioeconomic determinants of health disparities. An inductive content analysis was employed to identify how equity was assessed across studies. Results: We identified three key categories of metrics used to assess equity in medical crowdfunding: funding outcomes, campaign visibility, and donor participation. Across these domains, substantial disparities were observed. Campaigns in rural or economically disadvantaged areas tended to have lower success rates. Racial and ethnic inequities were consistently documented, with non-white individuals receiving fewer and smaller donations than white counterparts. Gender disparities were complex, especially in transgender-related campaigns. Socioeconomic status and educational attainment were significantly associated with outcomes, accompanied by differences in access to social capital and the ability to craft persuasive narratives. In regions with high medical debt or limited insurance coverage, more crowdfunding campaigns appeared, but with lower overall success. These inequities were shaped and reinforced by platform algorithms and design features that privileged users with preexisting advantages. Conclusions: Rather than serving as a corrective to healthcare access gaps, medical crowdfunding often reflects and reinforces structural inequities. These findings challenge its portrayal as an equitable financing solution and highlight the need for policy interventions to ensure fairer access to healthcare resources.